Agrobiodiversity Index gridded datasets - Jones, Sarah K.; Estrada-Carmona, Natalia; Remans, Roseline (2022)
Gridded datasets used in Jones et al. (2021) paper 'Agrobiodiversity Index scores show agrobiodiversity is underutilized in national food systems'. Details of how datasets were made and underlying sources are provided in Jones et al. (2021) Supplementary Information. Datasets included: - H_2010_spam_V2r0_42c: crop commodity diversity (Shannon's diversity index) at 10x10km resolution, based on SPAM 2010 V2 physical area maps - sr_2010_spam_v2r0_42c: crop commodity richness at 10x10km resolution, based on SPAM 2010 V2 physical area maps - sr_2010_spam_v2r0_42c_maj22: locations of cropland with at least 22 crop commodities (1) versus cropland with <22 crop commodities at 10x10km resolution, based on SPAM 2010 V2 physical area maps - Livestock_8_shannons_LSU: livestock diversity (Shannon's diversity index) calculated from population numbers converted to standard livestock units at 1x1km resolution, based on Global Livestock of the World v3 - Fish_srichness raster: freshwater fish species richness per major river basin, based on Tedesco et al (2017) - CropPasture_2000_bool: locations where cropland and pasture co-exist (1) versus locations where either cropland OR pasture exist (0), at 10x10km resolution, based on cropland and pasture maps for the year 2000 available from EarthStat - esa2015_natag_1km_pc: percentage of natural or semi-natural vegetation within a 1x1km window around cropped pixels, based on European Space Agency Climate Change Initiative (ESA-CCI) land cover maps for 2015 Not uploaded (no post-processing so data can be accessed at source): - potential soil biodiversity index (see https://esdac.jrc.ec.europa.eu/content/global-soil-biodiversity-atlas) - tree cover on agricultural land (see Zomer et al. 2016 and https://apps.worldagroforestry.org/global-tree-cover/index.html) (2021-09-06)